Estimation of exposure rate to nuclear medicine personnel during cardiac spect imaging using direct and indirect methods: a phantom study - Mubin, Zuraida Ab (Universiti Sains Malaysia, 2015)
This study was to determine the exposure rate to personnel during the 99mTc cardiac SPECT imaging procedure using direct and indirect methods. In this study, the single head gamma camera model Symbia-E manufactured by Siemens and the dual head gamma camera model Philips Adac Forte were used to scan the cardiac phantom. The direct method was conducted by measuring the exposure rate from radioactive cardiac phantom using Victoreen 451P-RYR survey meter at various distances (0.5 m, 1.0 m, 1.5 m and 2.0 m). The indirect method was based on mathematical model of exposure rate. The results indicated that exposure rates from direct method were higher than indirect method for both single and dual head gamma camera. The percentage differences between direct and indirect method for 23.71 mCi 99mTc for single head cardiac SPECT imaging at various distances were between 57.35% and 75%. For 21.80 mCi 99mTc, the percentage differences were between 29.20% 19.70% and 50%. On the other hand, The percentage differences between direct and indirect method for 23.71 mCi 99mTc for dual head cardiac SPECT imaging were between 41.20% and 50%. For 21.80 mCi 99mTc, the percentage differences were between 16.70% and 48.70% and for 19.89 mCi 99mTc, the percentage differences were between 20% and 52.10%. As conclusion, the calculated exposure from indirect method for both single and dual head cardiac SPECT imaging were lower than the actual exposure obtained from a direct method. Measurement of the exposure rates received from the cardiac phantom is important to ensure minimal hazard to personnel in nuclear medicine department and to propose a safe working protocol for personnel performing cardiac SPECT imaging.